Public Relations in Consultancy Practice: Empirical Insights from Ghana - Dowuona-Hammond , Margaret; Amo-Mensah, Mavis (Archives of Business Research, 2022)
This paper presents findings of a study on the nature of Public Relations (PR) in consultancy practice. The qualitative study specifically focused on case studies of three top PR management consultancies in Ghana. Drawing on the excellence theory as framework, the study involved in-depth interviews with a purposive sample of corporate communication managers from the three consultancies and review of corporate documents. The results suggest that the nature and dynamics of PR services provided in the three consultancies were similar although there were some notable variations in practice relative to patterns of work, account processes and fee structures. There were skilled professionals in the consultancies who offer a vast range of managerial PR services, predominantly on reputation management issues both offline and online, in addition to other technical functions. The study also established that the consultancies build strategic alliances and relationships with global holding companies to improve their competitive positioning and also create a wider network of diverse clientele. There is evidence that the consulting part of PR is currently booming. However, research on PR in consultancy practice has largely been neglected in the mainstream PR scholarship. The findings of the study, therefore, have implications for consulting firms recruiting PR professionals as well as consultants focusing on PR strategies and campaigns for their clients. The study also offers critical reflections on how PR strategies can effectively contribute to consultancy knowledge and practice beyond the Western context. The findings are original since no such research has previously been explored in Ghana.